2014
DOI: 10.1016/j.bbamem.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Branched amphiphilic peptide capsules: Cellular uptake and retention of encapsulated solutes

Abstract: Branched amphiphilic peptide capsules (BAPCs) are peptide nanospheres comprised of equimolar proportions of two branched peptide sequences bis(FLIVI)-K-KKKK and bis(FLIVIGSII)-K-KKKK that self-assemble to form bi-layer delimited capsules. In two recent publications we described the lipid analogous characteristics of our BAPCs, examined their initial assembly, mode of fusion, solute encapsulation, and resizing and delineated their capability to be maintained at a specific size by storing them at 4 °C. In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(80 citation statements)
references
References 69 publications
3
77
0
Order By: Relevance
“…These specimens (shown in Figs. 1, 2, 7, 8; Supplementary Video S3) were fed for three days on an orange tree sprig submerged in BAPC (Branched Amphiphilic Peptide Capsules) linked to Hg as a contrast agent 104 . They were rinsed three times www.nature.com/scientificreports www.nature.com/scientificreports/ in 30% ethanol (10 min for each rinse), dehydrated in an ethanol series (30 min per step, 50%, 70%, 80%, 90%, 95%, and three times at 100%), chemically dried by submersion in 2 ml of 100% hexamethyldisilazane (HMDS) for 2 hours and dried overnight at 35 °C.…”
Section: Methodsmentioning
confidence: 99%
“…These specimens (shown in Figs. 1, 2, 7, 8; Supplementary Video S3) were fed for three days on an orange tree sprig submerged in BAPC (Branched Amphiphilic Peptide Capsules) linked to Hg as a contrast agent 104 . They were rinsed three times www.nature.com/scientificreports www.nature.com/scientificreports/ in 30% ethanol (10 min for each rinse), dehydrated in an ethanol series (30 min per step, 50%, 70%, 80%, 90%, 95%, and three times at 100%), chemically dried by submersion in 2 ml of 100% hexamethyldisilazane (HMDS) for 2 hours and dried overnight at 35 °C.…”
Section: Methodsmentioning
confidence: 99%
“…As showed by Sukthankar et al 198 nanocapsules are formed with an average diameter of 20–30 nm with an internal volume of 4000 nm 3 allowing them to be considered as possible candidates for the encapsulation of a large number of different molecules including proteins. For this purpose BAPCs were used to encapsulate TAMRA-labeled TRNase A (RNase A, 13.7 kDa) and TAMRA-labeled cytochrome c (Tcytc, ~12 kDa).…”
Section: Studies On Branched Amphiphilic Peptide Capsilesmentioning
confidence: 99%
“…To date 198 , ( in vitro ) we have been able to load the BAPCs with 225 Ac that have stably retained ≥95% of their activity over 7 days, and shown that cultured cells readily take-up non-lethal concentrations of encapsulated 225 Ac. In vivo (Fig.…”
Section: Studies On Branched Amphiphilic Peptide Capsilesmentioning
confidence: 99%
“…Injection directly into the 4 th and 5 th nymphs, pupae, or adults proved to be easier, and more effective (Hunter, Gonzalez, Tomich 2018). Because previous research with BAPC-assisted delivery of dsRNA and plasmids resulted in efficient delivery into insects and animal cells in cultures (Avila et al, 2018; Sukthankar et al, 2014), an experiment was designed to evaluate the incorporation of BAPC to improve delivery of CRISPR/Cas9 components into arthropod ovaries of adult hemipterans (Psyllids and Leafhoppers) for heritable embryonic gene editing.…”
Section: Introductionmentioning
confidence: 99%